Development of a Starter with Protective Systems for a Three-Phase Induction Motor - Hope Orovwode; Simeon Matthew; A. Felix Agbetuyi; U. Anthony Adoghe; Elizabeth Amuta (Journal of Engineering)
Frequent burning of three-phase induction motors windings has been reported. The initial symptoms observed before the burning of the windings were an increase in operating current and a temperature rise. The induction motor protection and control system was designed, developed, and constructed to reduce the problem of burnt winding by early detection and disconnection of supply if the problem persists. It was found to be efficient, reliable, durable, and rugged. The system is a boost to Nigerian industrialists as it will reduce cases of burning of induction motors and the consequent downtime and cost. The system is cheap and easy to repair and maintain because the parts and components used in the design are available locally.